The influence of leadership and organizational culture on the performance of state primary school teachers Tembilahan district Indragiri Hilir regency - Syafaruddin; Isjoni; Elfis Suanto (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2024)
This research analyses leadership and organizational culture's vivacious and significant influence on teacher performance in public elementary schools in Tembilahan District, Indragiri Hilir Regency. The background of this research is based on a description of the performance of state elementary school teachers in Tembilahan District, Indragiri Hilir Regency. The type of research carried out is survey research with a quantitative research approach. The population in this study was 73 elementary school teachers. The sample used in the research was 73 people. The sampling technique uses total sampling. Data collection techniques are documentation and questionnaires. The data analysis used is descriptive statistics and inferential statistics. The research results show that the influence of the principal's leadership and organizational culture on the performance of public elementary school teachers is 92.8%, and the remainder is determined by other factors that are not part of this research. The research conclusions show the influence of the principal's leadership and organizational culture on the performance of state elementary school teachers in Tembilahan District, Indragiri Hilir Regency.